Conjuntos habitacionais e espaços livres : correlações socioespaciais e orientações projetuais - Ayoub, Thamine de Almeida Ayoub (2014)
This work is founded upon evidence drawn from the building process of Brazilian social interest housing estates, in which the pursuit for maximum housing unit acquisitions is the main goal, to the detriment of the conception of public spaces. On the other hand, it is understood that in residential areas with prevailing minimal size land and housing units, the appropriation of available public spaces to enlarge the private area is intensified. This fact prompts the need to review the ways such spaces are created. With this viewpoint, the study in this work is aimed at establishing guidelines for design of free spaces, specifically the squares, located at social interest housing estates, in search of offering the physical support required to fulfill their social roles in the context of a neighborhood. To that end, a review of literature is performed to initially obtain an amount of theoretical fundaments to be progressively enhanced by a prescriptive referential to enable the research object to be properly appraised and the project for residential squares to be adequately explained. Field research into squares located in housing states in the city of Londrina are conducted to validate the aforementioned guidelines by applying the theoretical principles earned from the process. Collected data are organized to allow for their analysis in temporal, socio-cultural and physical spatial axes, for further comparative evaluation as a means to identify the physical spatial project most suitable to the socio-cultural context encountered in squares located at social interest housing estates